Patterns of protein synthesis in the budding yeast cell cycle: variable or constant? - Eun-Gyu No; Heidi M Blank; Michael Polymenis (Microbial Cell)
Proteins are the principal macromolecular constituent of proliferating cells, and protein synthesis is viewed as a primary metric of cell growth. While there are celebrated examples of proteins whose levels are periodic in the cell cycle (e.g., cyclins), the concentration of most proteins was not thought to change in the cell cycle, but some recent results challenge this notion. The ‘bulk’ protein is the focus of this article, specifically the rate of its synthesis, in the budding yeast Saccharomyces cerevisiae.